2019
DOI: 10.1039/c9nj03144h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and microwave assisted extraction as rapid and efficient techniques for plant mediated synthesis of quantum dots: green synthesis, characterization of zinc telluride and comparison study of some biological activities

Abstract: In this study, a simple, rapid, and efficient plant-mediated green approach was presented for the synthesis of stable and ultra-small zinc telluride quantum dots (ZnTe QDs) using the aqueous extract of the Ficus johannis plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It was supposed that it was the viscosity reduction that allowed MA-OHE to be able to release antioxidant compounds, which resulted in a higher antioxidant activity for MA-OHE, compared with raw O. humifusa. Moreover, it was demonstrated that the plant extract-based CDs prepared by the microwave-assisted process had low toxicity [22]. Overall, the microwave-assisted extraction method helped to maintain nutrition, improve texture and appearance, and reduce viscosity relative to the conventional extraction methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was supposed that it was the viscosity reduction that allowed MA-OHE to be able to release antioxidant compounds, which resulted in a higher antioxidant activity for MA-OHE, compared with raw O. humifusa. Moreover, it was demonstrated that the plant extract-based CDs prepared by the microwave-assisted process had low toxicity [22]. Overall, the microwave-assisted extraction method helped to maintain nutrition, improve texture and appearance, and reduce viscosity relative to the conventional extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cytotoxicity results indicated that MA-OHE possessed greater biocompatibility than did the raw O. humifusa, slightly reducing the cell survival of HaCaT cells from 87.47 ± 1.60 and 80.88 ± 4.84% after 24 h treatment at 100 µg/mL. A possible explanation was that under high-temperature and high-energy treatment, the raw O. humifusa was transformed into carbon dots (CDs) [22] and significantly reduced the viscosity. It was supposed that it was the viscosity reduction that allowed MA-OHE to be able to release antioxidant compounds, which resulted in a higher antioxidant activity for MA-OHE, compared with raw O. humifusa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of colloidal inorganic nanoparticles (NPs) including catalytic, electronic, optical, and magnetic performances are greatly affected by their morphologies, suggesting opportunities for enabling applications, which are not possible by poorly defined or bulk materials [1–5] . In recent years, the morphology and according properties of Zn– and Cd–chalcogenide compositions have been exploited and rationalized [6–15] . Nevertheless, their further development into particular applications are somewhat limited by the concerns of fabrication technique for complex (hetero)structures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In recent years, the morphologya nd according properties of Zn-and Cd-chalcogenide compositions have been exploited and rationalized. [6][7][8][9][10][11][12][13][14][15] Nevertheless, their furtherd evelopment into particular applications are somewhat limited by the concerns of fabrication technique for complex (hetero)structures. To circumvent this obstacle, an attractive alternative strategy is cation exchange (CE).…”
Section: Introductionmentioning
confidence: 99%